2020
DOI: 10.1016/j.jtice.2020.08.015
|View full text |Cite
|
Sign up to set email alerts
|

Exploring community evolutionary characteristics of microbial populations with supplementation of Camellia green tea extracts in microbial fuel cells

Abstract: Highlights Unveil microbial community evolution of Camellia tea-supplemented MFCs. Exhibit interactions of GT's electron shuttles and toxicity potency upon MFCs. Disclose electrochemical criteria to switch Camellia antioxidants to be ESs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…Stably reversible profiles of ESs or gradually attenuated sketches of antioxidants from distinct herbal extracts could suggest whether such herbal extracts were sustainable or unendurable for bioenergy/biorefinery applications, respectively. As prior studies [ 39 , 40 ] revealed, comparison upon more than 20 species of refreshing medicinal herbs indicated that electroactive medicinal herbs- Syzygium aromaticum (Dıng xiang), Citrus reticulate (Chenpí) and Lonicera japonica (Jınyín hua) and Camellia green tea ( Camellia sinensis (L.) Kuntze) were the most electroactive medicinal herbs due to the greatest area and most significant redox potential peaks displayed in CV profiles. As recent novel findings disclosed [11] , chemicals bearing ortho or para dihydroxyl substituents on benzene ring and the flavonoid structure(s) would be the most favorable to mediate electron-shuttling features for bioenergy stimulation and antiviral “catalysis”.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Stably reversible profiles of ESs or gradually attenuated sketches of antioxidants from distinct herbal extracts could suggest whether such herbal extracts were sustainable or unendurable for bioenergy/biorefinery applications, respectively. As prior studies [ 39 , 40 ] revealed, comparison upon more than 20 species of refreshing medicinal herbs indicated that electroactive medicinal herbs- Syzygium aromaticum (Dıng xiang), Citrus reticulate (Chenpí) and Lonicera japonica (Jınyín hua) and Camellia green tea ( Camellia sinensis (L.) Kuntze) were the most electroactive medicinal herbs due to the greatest area and most significant redox potential peaks displayed in CV profiles. As recent novel findings disclosed [11] , chemicals bearing ortho or para dihydroxyl substituents on benzene ring and the flavonoid structure(s) would be the most favorable to mediate electron-shuttling features for bioenergy stimulation and antiviral “catalysis”.…”
Section: Resultsmentioning
confidence: 98%
“…In our previously studies indicated that Camellia green tea extract has more stimulate bioenergy utilization (e.g., 176% increase in maximum power density) using MFC, especially unfermented Camellia tea extract (i.e. green tea) has the ESs for increasing bioenergy extraction compared to other herbs [ 6 , 53 ]. The major constituent EGCG of green tea showed that anti-COVID-19 activity which could activate Nrf2 pathway and suppress ACE2 and TMPRSS2 [54] .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The selection of pertinent RMs should not only regard their excellent redox. (82) In this experiment, the wheat straw hydrolysate was used for electricity generation and its microbial communities were checked. The results indicate a potential substrate utilization process in which suspended bacteria and biofilm break down the complex fuel into simple fermentation products, which can further be utilized by anode electrochemical bacteria to generate electricity.…”
Section: Ecs Transactions 107 (1) 10729-10755 (2022)mentioning
confidence: 99%
“…are prepared industrially by utilizing microorganisms, e.g. algae, cyanobacteria, and eukaryotic microalgae, that have metabolic characteristics and are useful in biofuel manufacturing (Bruzaite et al, 2020;Majidian et al, 2018;Qin et al, 2020;Sartaj et al, 2020). Bio-nanoconvection dynamics involving microorganisms have tremendous medical applications and are of significant importance as a tactic in removing/reducing/controlling microorganism activities in human health (Basha & Sivaraj, 2021;Bhatti, Marin, et al, 2020;Waqas et al, 2019).…”
Section: Introductionmentioning
confidence: 99%